Laws of Heat Radiation from Spherical Gas Volumes. Part I. Laws Formulation - Makarov, Prof. Dr. A. N. (International Journal of Advanced Engineering Research and Science, 2020)
In 2014-16 the author of this article disclosed the laws of heat radiation from isothermal isochoric concentric spherical gas volumes, that the article presents. Radiating gas volumes of any complex form can be entirely filled by concentric spherical together with coaxial cylinder gas volumes and calculate heat radiation from gas volumes, furnace torches, fire boxes, combustion chambers on the heating surfaces with high accuracy.